2023
DOI: 10.1140/epjc/s10052-023-11805-3
|View full text |Cite
|
Sign up to set email alerts
|

Traversable Morris–Thorne–Buchdahl wormholes in quadratic gravity

Abstract: The special Buchdahl-inspired metric obtained in a recent paper [Phys. Rev. D 107, 104008 (2023)] describes asymptotically flat spacetimes in pure $$\mathcal {R}^{2}$$ R 2 gravity. The metric depends on a new (Buchdahl) parameter $$\tilde{k}$$ k ~ of higher-derivative characterist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 67 publications
1
13
0
Order By: Relevance
“…Expression (24) is a special case of the generalized Campanelli-Lousto solution that we reported for Brans-Dicke gravity [22]. This relationship between the two solutions further highlights the shared characteristics of pure  gravity and Brans-Dicke gravity.…”
Section: Buchdahl-inspired Solutionssupporting
confidence: 58%
See 2 more Smart Citations
“…Expression (24) is a special case of the generalized Campanelli-Lousto solution that we reported for Brans-Dicke gravity [22]. This relationship between the two solutions further highlights the shared characteristics of pure  gravity and Brans-Dicke gravity.…”
Section: Buchdahl-inspired Solutionssupporting
confidence: 58%
“…The metric given in equation (22) possesses two additional noteworthy properties: (I) Non-triviality of the asymptotically flat Buchdahl-inspired metric: The metric in (22) is Ricci-scalar flat, viz. º " Î +  r 0  .…”
Section: Buchdahl-inspired Solutionsmentioning
confidence: 99%
See 1 more Smart Citation
“…This latter solution is asymptotically de Sitter, and is specified by four parameters, reflecting the fourth-derivative nature of a quadratic theory). Upon another coordinate transformation [22] 1 −…”
Section: The Special Buchdahl-inspired Metric: Brief Reviewmentioning
confidence: 99%
“…The metric is dependent on a new (Buchdahl) parameter k of higher-derivative characteristic, and recovers the Schwarzschild metric when k = 0. In a recent work [22], it was demonstrated that the special Buchdahl-inspired metric supports a two-way traversable Morris-Thorne-Buchdahl (MTB) wormhole for k ∈ (−1, 0), in which case the weak energy condition is formally violated.…”
Section: Introductionmentioning
confidence: 99%